Impact of role-playing activities in social awareness. - Moreno Ortiz, Paula Andrea; Prada Ramírez, Tatiana; Triviño Guevara, Laura Juliana (Corporación Universitaria Minuto de Dios, 2017)
During this research, the topic of social awareness was developed with second and third semester students at Corporación Universitaria Minuto de Dios. The objective of this research was that participants faced role-plays where they could find common situations as bullying, lack of respect, injustice or intolerance with others; with the purpose that they become aware of the importance that values as respect, tolerance, justice, and honesty have in their lives. In first place, the constructs are developed: role-playing, social awareness and material’s design that supported the research and were the principal elements that participants developed during the research; it is because the first one were the activities that participants had to do during the session, the second one was the knowledge that the participants had about values and how those values help them to be part of the society, and the last one was the steps and the guidelines that were followed in order to create the activities.
Keywords: Conciencia Social; Acoso; Valores Humanos; INGLES – ANÁLISIS GRAMATICAL; VALORES; INGLES; ÉTICA